2005
DOI: 10.1007/s00170-004-2317-y
|View full text |Cite
|
Sign up to set email alerts
|

Integration of process planning and scheduling in a job shop environment

Abstract: Today's manufacturing systems are striving for an integrated manufacturing environment. To achieve truly computerintegrated manufacturing systems (CIMS), the integration of process planning and production scheduling is essential. This paper proposes a framework for integration of process planning with production scheduling in a job shop environment for axisymmetric components. Based on the design specifications of incoming parts, feasible process plans are generated taking into account the real time shop floor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…At the beginning of the research on the IPPS problem, process planning and scheduling are integrated in a sequential manner [13]; this paradigm takes no advantage of the flexibilities in both the process planning module and the scheduling module since there are still serious bottlenecks in actual manufacturing activities. After that, relative research tends to integrate the two functions coherently to achieve a superior overall system performance mainly by three means: (1) mathematical modelling and corresponding solutions; (2) meta-heuristic-based approaches, such as genetic algorithm (GA); and (3) other approaches, e.g., agent-based methods [14].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning of the research on the IPPS problem, process planning and scheduling are integrated in a sequential manner [13]; this paradigm takes no advantage of the flexibilities in both the process planning module and the scheduling module since there are still serious bottlenecks in actual manufacturing activities. After that, relative research tends to integrate the two functions coherently to achieve a superior overall system performance mainly by three means: (1) mathematical modelling and corresponding solutions; (2) meta-heuristic-based approaches, such as genetic algorithm (GA); and (3) other approaches, e.g., agent-based methods [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to such limitations and shortcomings in applications of FMSs, relative studies on integrated process planning and scheduling have been performed to achieve an efficient use of an FMS. According to existing publications [8][9][10][11][12][13][14][15][16], corresponding research on integrated process planning and scheduling (IPPS) are quite fruitful, and significant improvements have been achieved with the objective of makespan minimization, which is a primary criterion to evaluate the effectiveness of a schedule scheme. For instance, Doh et al [10] adopted the priority dispatch rules to quickly determine a feasible scheduling scheme; nevertheless, this method usually cannot ensure a competitive solution.…”
Section: Introductionmentioning
confidence: 99%
“…If we look at the early works on IPPS problem, we can see the following literature on this problem; Nasr and Elsayed [10], Hutchinson et al [11], Chen and Khoshnevis [12], Zhang and Mallur [1], Brandimarte [13], Morad and Zalzala [14]. After these studies more works are done on IPPS such as: Ming and Mak [15], Tan and Khoshnevis [16], Kim et al [17], Kumar and Rajotia [18], Lim and Zhang [19], Tan and Khoshnevis [20], Kumar and Rajotia [21], Moon et al [22], Guo et al [23], Leung et al [24], Phanden et al [25], Petrovic et al [26], Zhang et al [27], and Zhang and Wong [28]. Scheduling with due date assignment is also popular research topic which is extensively studied in the literature.…”
Section: Literature Surveymentioning
confidence: 99%
“…They concluded that the proposed method helps in on-line determination and assignment of loads on various machines. Further, Kumar and Rajotia, (2006) presented a scheme for integration model for job-shop. It considered machine capacity and cost while assigning operation to machines.…”
Section: Non-linear Process Planning and Scheduling Approachmentioning
confidence: 99%